2006
DOI: 10.1097/00006199-200601000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Fatigue, Influencing Variables, and Consequences in Chronic Obstructive Pulmonary Disease

Abstract: Fatigue is an important problem that affects performance of daily activities in people with COPD. The relationships or interactions that exist among fatigue and other symptoms are complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
147
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(164 citation statements)
references
References 27 publications
13
147
2
2
Order By: Relevance
“…If dyspnea increases the work of breathing and requires greater energy, it presumably will lead to greater fatigue and therefore, influence the person's perception of their health. Although the correlation coefficient between dyspnea and fatigue was only .41 in this study, other studies have reported a strong relationship between the two sensations, with some patients not being able to distinguish between the two symptoms (Janson-Bjerkelie, KohlmanCarrieri, & Hudes, 1986;Kapella, Larson, Patel, Covey, & Berry, 2006). Interestingly, a recent study of symptom clusters in patients with advanced chronic diseases showed that worse dyspnea was associated with poor health ratings even after adjusting for the effects of six other symptoms including fatigue (Walke, Byers, Gallo, Endrass, & Fried, 2007).…”
Section: Discussioncontrasting
confidence: 73%
“…If dyspnea increases the work of breathing and requires greater energy, it presumably will lead to greater fatigue and therefore, influence the person's perception of their health. Although the correlation coefficient between dyspnea and fatigue was only .41 in this study, other studies have reported a strong relationship between the two sensations, with some patients not being able to distinguish between the two symptoms (Janson-Bjerkelie, KohlmanCarrieri, & Hudes, 1986;Kapella, Larson, Patel, Covey, & Berry, 2006). Interestingly, a recent study of symptom clusters in patients with advanced chronic diseases showed that worse dyspnea was associated with poor health ratings even after adjusting for the effects of six other symptoms including fatigue (Walke, Byers, Gallo, Endrass, & Fried, 2007).…”
Section: Discussioncontrasting
confidence: 73%
“…This result is consistent with previous studies that have noted significant relationships between dyspnea and fatigue [55][56][57][58]. Also Kapella et al, (2006) [59] reported that there was significant correlation between dyspnea and fatigue scores among the COPD patients.…”
Section: Discussionsupporting
confidence: 92%
“…This is important to recognize as there exists a strong relationship between respiratory symptoms and fatigue [29]. Fatigue has been reported to have a strong, direct and negative effect on functional performance [30] and per se will affect physiologic tests such as a six-minute walk testing. To the best of our knowledge this is the first study to utilize the Fatigue Severity Scale to study fatigue across a multifaceted advanced lung disease population.…”
Section: Discussionmentioning
confidence: 99%